Resiko Ulkus Kaki Diabetes pada Petani di Wilayah Kerja Puskesmas Palengaan Kabupaten Pamekasan Madura - Muhammad Rofiqi; Jon Hafan Sutawardana; Kushariadi Kushariadi (Pustaka Kesehatan, 2022)
A diabetic foot ulcer is one of the complications of diabetes mellitus. The farmer is a job that is at risk of developing diabetic ulcers, especially farmers with diabetes. Farmers pay less attention to protecting their feet, so they risk foot trauma. This study aimed to describe the risk of diabetic foot ulcers in farmers. In this descriptive observational study in the working area of Community Health Center of Palengaan Pamekasan Madura, 76 farmers were selected by purposive sampling. All of the respondents were examined within low's 60-second diabetic foot instrument. The data were analyzed with univariate analysis. This study found that 72.4% of farmers had a moderate risk of developing diabetic ulcers and 11,8% of patients were at risk for severe foot ulcers. Most farmers are at high risk of developing diabetic foot ulcers. Therefore, farmers with diabetes need special attention from nurses in providing education on the importance of foot protection when working